LEGAL CONSEQUENCES OF VIOLATION OF NON DISCLOSURE AGREEMENT OBLIGATIONS AS IMPLEMENTATION OF LEGAL PROTECTION AGAINST TRADE SECRETS - I Nyoman Sudana; I Nyoman Bagiastra (Transpublika Publisher, 2024)
This high percentage of potential leakage of trade secret information that has economic value from a company can occur either from parties within the company or from parties outside the company if there is no commitment to safeguard the information. The purpose of this writing is to analyze the regulations regarding non-disclosure agreements in trade secrets law and to examine the legal consequences of violations of these agreements. The benefit of this writing is to provide a juridical understanding of the regulation of non-disclosure agreements in efforts to protect trade secrets, as well as to offer scientific contributions in the dimension of legal science related to the regulation of non-disclosure agreements. This study is based on the vagueness of norms, utilizing a type of normative legal research through a legislative approach and analyzed using descriptive and argumentative techniques. The research results show that non-disclosure agreements are not specifically regulated but are generally addressed in trade secrets law. In terms of legal consequences arising from non-fulfillment of the agreement, there are criminal sanctions, including a maximum prison sentence of 2 years and/or a fine of Rp. 300,000,000, as well as civil sanctions in the form of compensation imposed on parties who harm the company. It would be better if non-disclosure agreements were explicitly regulated by law to strengthen their legal force and provide legal certainty for the parties involved in the agreement.